Pembelajaran Project Based Learning Memanfaatkan Aplikasi TikTok untuk Meningkatkan Kreativitas Rias Wajah Dasar Korektif - Arisa, Ma’rifani Fitri (Universitas Nusantara PGRI Kediri, 2023)
The TikTok application is popular with the public as an information medium. The TikTok application is used by students, the TikTok application has makeup filters that can be a source of basic corrective makeup course makeup ideas. This can be a medium of learning so that students become interested. This study aims to utilize TikTok in the learning process by implementing project based learning in basic corrective makeup courses. This study used descriptive qualitative method. In this study using observation techniques, interviews and documentation studies. The findings of this study can describe (1) the reasons for lecturers using the TikTok makeup filter application as a source of makeup inspiration, and applying a project based le arning model so that learning is interesting and accepted by students. (2) The results of utilizing the TikTok makeup filter application have an influence on the learning process in achieving goals and effectiveness in basic corrective makeup courses (3) Obstacles and efforts in utilizing the TikTok makeup filter application, namely an unstable network.